Association between seasonal influenza vaccination with pre- and postnatal outcomes. Issue 13 (22nd March 2019) - Getahun, Darios; Fassett, Michael J.; Peltier, Morgan R.; Takhar, Harpreet S.; Shaw, Sally F.; Im, Theresa M.; Chiu, Vicki Y.; Jacobsen, Steven J.
Abstract: Objective: Influenza vaccination during pregnancy is known to prevent severe influenza illness but its effects on other outcomes and the extent to which its safety is affected by timing of vaccination, maternal race/ethnicity and the type of vaccine is less clear. Therefore, we examined this in a large retrospective cohort. Methods: We analyzed medical and vaccination records from the Kaiser Permanente Southern California (KPSC) records and from the Kaiser Immunization Tracking System (2008–2016). The study included women who were pregnant with singletons during the influenza season. Odds ratios (OR) and their 95% confidence intervals (CI) were used to quantify the associations between immunization status during pregnancy and prenatal and postnatal outcomes after adjusting for confounders. Results: Of the 247, 036 women in these analyses, 53% were vaccinated during their pregnancy. No association between influenza vaccination during pregnancy and adverse prenatal and neonatal outcomes were observed. Influenza vaccination is associated with reduced risk of influenza (OR: 0.49, 95% CI: 0.39–0.62), maternal fever (OR: 0.40, 95% CI: 0.35–0.45), preeclampsia (OR: 0.93, 95% CI: 0.90–0.96), placental abruption (OR: 0.89, 95% CI: 0.82–0.96), stillbirth (OR: 0.88, 95% CI: 0.78–0.99), and NICU admission (OR: 0.89, 95% CI: 0.87–0.92). Both active and inactive vaccines were found to be safe in vaccinated pregnant women regardless of timing of vaccination. Conclusions: This study found no evidence of adverse maternal and infant outcomes associated with seasonal influenza vaccine during pregnancy. On the contrary, vaccinated women were less likely to have adverse outcomes than unvaccinated women. The lack of increased adverse outcomes associated with influenza vaccination suggests that the benefits of vaccination during pregnancy to the woman and her child far outweigh any risk, if there is one, from the vaccination.